The construction method for staircase and floor slab / Atiqah Wajihah Jaffri - Jaffri, Atiqah Wajihah (2021)
Slab is an important element in a building including the stairs as well. The importance of slab is the space between the slab and the ceiling can be used to place the utilities of the building and the upper slab can also be used as a ceiling for the floor below. Meanwhile, the purpose of the stairs is to provide an easy access to move from one level to another. Therefore, this report will explained about the construction method of slab and stairs as it is very important when it comes to ensuring the health and safety of a building site. The objective of this report is to identify the purpose of staircase and floor slab in building. To study the construction method for staircase and floor slab and to determine the problems and solutions due to the construction of slab and staircase.